The Challenges to Make Decent Work a Reality for Domestic Workers in Brazil (Global Journal of Human-Social Science, 2023)
The present paper deals with the problematic of labor and social security rights of domestic workers in Brazil and around the world highlighting the importance of more inclusive and fair public policies and private actions for this category of workers The research analyzed official documents and statistics as well as bibliographic research from authors who discuss the subject
Keywords: paid domestic work; social protection; decent work